2021
DOI: 10.1590/1678-4499.20200276
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane pre-sprouted seedlings produced with beneficial bacteria and arbuscular mycorrhizal fungi

Abstract: The demand for the increased productivity of sugarcane crops has required changes in its production chain, such as the use of pre-sprouted seedlings (PSS) of sugarcane into the chain. In this system, the inoculation of beneficial microorganisms, such as plant growthpromoting bacteria (PGPB) and arbuscular mycorrhizal fungi (AMF), can improve seedling development. The objective was to evaluate the beneficial effect of PGPB and AMF inoculation on sugarcane PSS production system. Experiments were carried out in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…In the absence of inoculation, PSS survival of 82.4% corroborates with the results found by Almeida Neto et al [67]. Although no other studies evaluate PSS survival in the field under the use of microorganisms, studies reported the PGPB action in improving rooting and nutritional aspects [37,[68][69][70][71].…”
Section: Discussionsupporting
confidence: 86%
“…In the absence of inoculation, PSS survival of 82.4% corroborates with the results found by Almeida Neto et al [67]. Although no other studies evaluate PSS survival in the field under the use of microorganisms, studies reported the PGPB action in improving rooting and nutritional aspects [37,[68][69][70][71].…”
Section: Discussionsupporting
confidence: 86%
“…Apical propagules have a higher sprouting rate than basal propagules due to their physiological age and greater metabolic activity (Baracat et al 2017;Figueiredo et al 2020). The vegetal growth in sugarcane can be improved with the application of organic fertilizers (Gazola et al 2017); isolated plant growth-promoting bacteria (PGPB) (Almeida et al 2024), combined with humic acids (Oliveira et al 2018), in association with arbuscular mycorrhizal fungi (Rossetto et al 2021); or through microalga biomass (Mógor et al 2022). Microalgae brings advantages to the economy and environment sustainability, producing a variety of agricultural products (Kapoore et al 2021;Parmar & Srivatsan 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Microbes with potential to be used as biofertilizers can promote coffee growth by improving plant mineral nutrition and phytohormones production or by inhibiting plant pathogens and pests (Vallejos-Torres et al 2021). Plant growth-promoting bacteria and arbuscular mycorrhizal fungi (AMF) are the most promising microorganisms for sustainable agriculture (Cipriano et al 2021, Rossetto et al 2021. AMF can enhance the uptake of relatively immobile nutrients, particularly phosphorus (P), but also nitrogen (N) and other nutrients, from the soil to the host plant via the extraradical mycelium (ERM) (Bennett and Groten 2022).…”
Section: Introductionmentioning
confidence: 99%